DESIGN OF SUPERSTRUCTURES, SUBSTRUCTURES, RAIN WATER TANK, AND FLOOD ANALYSIS OF AULA KONSER MUSIK POP GEDEBAGE BANDUNG - Adiputra, Julian
Infrastructutre project has to had a good plan and design to ensure the construction process and function of the infrastructure reach its goal. One of the field of planning and design in this final assignment, Aula Konser Musik Pop Gedebage Bandung, is structural design and design of water resources field. Structural field consists of design of superstructure and design of substructure, while water resources field consists of design of rain water tank and flood analysis. The designed structure is separated into big building superstructure, small building superstructure, and basement. Structural system used for big building superstructure and basement is dual system of special reinforced concrete moment frame and special structural wall, while the structural system used for small building superstructure is special reinforced concrete moment frame. The applied loads for designing this building refer to SNI 1727:2013 “Beban Minimum untuk perancangan bangunan gedung dan struktur lain”, and ASCE 7-10 “Minimum design loads for building and other structures”. Design process of this building refers to SNI 1726:2012 “Tata cara perencanaan ketahanan gempa untuk struktur bangunan gedung dan non gedung”, SNI 2847:2013 “Persyaratan beton struktural untuk bangunan gedung”, ACI 318-99 “Building code requirements for structural concrete”, and AISC 1993 “Load and resistance factor design specification for structural steel buildings”. Design of rain water tank and flood analysis refers to SNI 2415:2016 “Tata cara perhitungan debit banjir”. The design products of this final project are 30 design of beams, 7 design of columns include the composite columns, 4 design of shearwalls, 3 design of slabs, shear connector design, stair design, tribune design, and ramp design. The results for water resources field are a rain water tank located in B3 and B4 basement, which dimension is 32m x 8m x 6.8m and according to flood analysis done, the dimension of the river can hold the flood discharge with return periode of 100 years